Made to crave : satisfying your deepest desire with God, not food - TerKeurst, Lysa. (Grand Rapids, Mich. : Zondervan, 2010)
Connects a woman's desire to be healthy and the spiritual empowerment necessary to make that happen, providing both diet inspiration and advice as well as Bible study to make healthy lifestyle changes.
Introduction: finding your "want to" -- What's really going on here? -- Replacing my cravings -- Getting a plan -- Friends don't let friends eat before thinking -- Made for more -- Growing closer to God -- I'm not defined by the numbers -- Making peace with the realities of my body -- But exercise makes me want to cry -- This isn't fair! -- Stinkin', rotten, horrible, no good day -- The curse of the skinny jeans -- Overindulgence -- Emotional emptiness -- The demon in the chips poster -- Why diets don't work -- The very next choice we make -- Things lost, better things gained -- Live as an overcomer.
Includes bibliographical references.
Keywords: Christian women -- Religious life; God (Christianity) -- Worship and love; Spirituality; Food -- Religious aspects -- Christianity